The inhibition mechanism of H2O at hydrothermal aging over Pt/SiO2-Al2O3 for NO oxidation. Issue 4 (August 2021) - Ding, Xinmei; Liu, Zhimin; Liang, Yanli; He, Darong; Yao, Pan; Lai, Xiaoxiao; Zhao, Ming; Wang, Jianli; Chen, Yaoqiang
Abstract: Pt/SiO2 -Al2 O3 (Pt/SA) is commonly used as diesel oxidation catalysts (DOC) in industry, but it could be seriously deactivated caused by H2 O at long-term high temperature. In this paper, the inhibition mechanism of water on Pt/SA for NO oxidation was studied. The fresh Pt/SA (Pt/SA-F) was treated in an air ﬂow with/without 10% H2 O at 700 °C for 10 h to obtain the hydrothermally/thermally aged catalysts named as Pt/SA-HA and -A, respectively. NO oxidation tests showed that Pt/SA-HA had lower activity than Pt/SA-A. A series of characterizations proved H2 O didn't affected Pt states and support structure as they were similar over two aged catalyst. 1 H NMR and In-situ DRIFTS testified that water deactivation was a result of the acidity loss of catalysts, which inhibited the decomposition and desorption of reaction intermediate, finally resulting in bad NO oxidation activity. Graphical Abstract: ga1 Highlights: H2 O inhibition mechanism at hydrothermal aging on Pt/SiO2 -Al2 O3 for NO oxidation was investigated. H2 O leaded to the loss of Brönsted acid sites (like-bridge Al-OH-Si). The loss of acid sites induced by H2 O suppressed decomposition of nitrate species resulting in low NO activity.